Ultrasound-Guided Caudal Block for Anal Canal Surgery : A Prospective Cohort Study (2018)
ABSTRACT: Introduction: Postoperative pain is an important symptom in patients after non-oncological anal canal surgery. A caudal block has shown to be an effective analgesic technique in this type of surgery, and ultrasound facilitates its performance and increases the rate of a successful block. We aimed to determine the effectiveness of ultrasound-guided caudal block (UGCB) in anesthesia and postoperative analgesia in patients scheduled for benign anal surgery. Methods: This was a prospective interventional cohort study in adult patients who underwent benign anal surgery under UGCB. We evaluated the effectiveness of the intervention based on postoperative pain intensity measured with the numeric rating scale (NRS) at the following postoperative time points: 6, 12 and 24 hours. The following outcomes were included in our analysis: lower limbs motor block, urinary retention, rescue analgesia, and patient’s analgesia satisfaction. Results: A total of 23 patients were included for data analysis. At least 65% of the study population reported none to mild pain (NRS ≤ 3) during the first 24 hours after surgery. None of the study patients experienced complete motor block in lower extremities or urinary retention. The mean time for patients to request the first rescue analgesia was 6.4 hours. The survey results indicated that 22 patients (95.7%) out of 23 were satisfied with the postoperative pain control. Conclusions: UGCB is an effective, easy to perform intervention in patients with benign anal canal surgery. This technique offers an alternative multimodal pain control therapy with satisfactory analgesic effect and low rate of adverse events.